2019
DOI: 10.1152/jn.00869.2016
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of vibrissal mechanical properties across the rat mystacial pad

Abstract: Recent work has quantified the geometric parameters of individual rat vibrissae (whiskers) and developed equations that describe how these parameters vary as a function of row and column position across the array. This characterization included a detailed quantification of whisker base diameter and arc length as well as the geometry of the whisker medulla. The present study now uses these equations for whisker geometry to quantify several properties of the whisker that govern its mechanical behavior. We first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…Although high speed 3D imaging in animals freely whisking at natural objects would be needed to better answer this question (Hobbs et al, 2015), the complex 3D structure of natural surfaces could lead to moments when select sets of non-adjacent whiskers could come into contact with objects. Additionally, whiskers are of variable length and physical properties (Yang et al, 2019) which could also lead to non-intuitive spatio-temporal sequences of whisker-object contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Although high speed 3D imaging in animals freely whisking at natural objects would be needed to better answer this question (Hobbs et al, 2015), the complex 3D structure of natural surfaces could lead to moments when select sets of non-adjacent whiskers could come into contact with objects. Additionally, whiskers are of variable length and physical properties (Yang et al, 2019) which could also lead to non-intuitive spatio-temporal sequences of whisker-object contacts.…”
Section: Discussionmentioning
confidence: 99%
“…It allows for the investigation of the facial skin and whisker pad completely deprived of afferent input. The whisker pad represents a sensory apparatus of huge interest in the fields of behavioral studies, cognitive plasticity and biomechanics (Guntinas-Lichius et al, 2002 ; Tomov et al, 2002 ; Seitz et al, 2011 ; Mameli et al, 2017 ; Yang et al, 2019 ). Furthermore, our denervation model prevents any aberrant reinnervation of the whisker pad from other afferent branches of the trigeminal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between kinematics and dynamics is primarily determined by material properties (density, Young's modulus, damping) of the whisker and is therefore dependent on the model assumptions for these parameter values. Previous work has found that density as well as Young's modulus vary between proximal and distal whisker regions (22,38,39). In WHISKiT Physics, parameters were chosen to be within the range of biological variation: density was approximated to increase linearly from base to tip, while Young's modulus and damping properties were assumed to be homogeneous within and across whiskers.…”
Section: Discussionmentioning
confidence: 99%